Predictors of outcome in a large retrospective cohort of patients with transverse myelitis. (November 2018) - Gastaldi, Matteo; Marchioni, Enrico; Banfi, Paola; Mariani, Valeria; Di Lodovico, Laura; Bergamaschi, Roberto; Alfonsi, Enrico; Borrelli, Paola; Ferraro, Ottavia Eleonora; Zardini, Elisabetta; Pichiecchio, Anna; Cortese, Andrea; et al.
Background: Transverse myelitis (TM) is an inflammatory disorder that can be idiopathic or associated with central nervous system autoimmune/dysimmune inflammatory diseases, connective tissue autoimmune diseases, or post-infectious neurological syndromes. Prognosis of initial TM presentations is uncertain. Objective: To identify outcome predictors in TM. Methods: Retrospective study on isolated TM at onset. Scores ⩾3 on the modified Rankin scale (mRS) marked high disability. Results: A total of 159 patients were identified. TM was classified as follows: idiopathic (I-TM, n = 53), post-infectious (PI-TM, n = 48), associated with multiple sclerosis (MS-TM, n = 51), or neuromyelitis optica spectrum disorders/connective tissue autoimmune diseases/neurosarcoidosis ( n = 7). At follow-up (median, 55 months; interquartile range, 32–80), 42 patients were severely disabled, and patients with I-TM or PI-TM showed the worst outcomes. Predictors of disability were infectious antecedents, sphincter and pyramidal symptoms, high mRS scores, blood–cerebrospinal fluid barrier damage, lumbar magnetic resonance imaging (MRI) lesions on univariate analysis, and older age (odds ratio (OR), 1.1; 95% confidence interval (CI), 1.0–1.1), overt/subclinical involvement of the peripheral nervous system (PNS) (OR, 9.4; 95% CI, 2.2–41.0), complete TM (OR, 10.8; 95% CI, 3.4–34.5) on multivariate analysis. Conclusion: Our findings help define prognosis and therapies in TM at onset. Infectious antecedents and PNS involvement associate with severe prognosis. Nerve conduction studies and lumbar MRI could improve the prognostic assessment of this condition.